Zakat institution’s governance in Malaysia : zakat payers’ perspective - Md Hairi, Md Hussain (2017)
Zakat payers’ confidence in zakat institutions is not at a satisfactory level although zakat collection increases every year. The issue of low public confidence is due to the weakness in the zakat institution’s governance. This study tried to explore the phenomena in the zakat institution’s governance and wished to accomplish two main objectives. The first objective was to identify the constitution of the zakat institution’s governance, while, the second objective was to examine the magnitude of the variables in the zakat institution’s governance. In this study, factors that constitute the zakat institution’s governance are discussed from the perspective of the stakeholder theory and the agency theory. The survey method was used for data collection. 431 questionnaires were fit to be analyzed using the exploratory factor analysis and the confirmatory factor analysis after passing the screening and purification process. This study found nine variables that constitute the zakat institution’s governance to address the first objective, while the second objective was addressed when these variables that were really strong in terms of reliability and validity were arranged according to their magnitude of strength. These variables were information technology (0.783), law (0.780), accountability (0.713), service quality (0.658), religiosity (0.649), participation (0.642), enforcement (0.607), audit committee independence (0.581) and audit committee diligence (0.514). The implications of this study contribute to the literature by enriching discussions on the zakat institution’s governance. Thus, understanding of the zakat institution’s governance can be improved since the findings are based on empirical evidence. Implications to the theory are in terms of the usage of the stakeholder theory and the agency theory in the zakat environment where previously these theories were only applicable in the corporate environment. This reinforces the application of these theories in environments of nonprofit organizations. These findings also contribute to zakat institutions by presenting the important factors that can assist in developing strategies to put zakat institution’s governance at the highest level.